Exploring the underlying mechanisms of obesity and diabetes and the potential of Traditional Chinese Medicine: an overview of the literature - Chen, Yan-kun; Liu, Ting-ting; Teia, Farah Khameis Farag; Xie, Meng-zhou (Frontiers in Endocrinology, 2023)
Obesity and diabetes are closely related metabolic disorders that have become major public health concerns worldwide. Over the past few decades, numerous studies have explored the underlying mechanisms of these disorders and identified various risk factors, including genetics, lifestyle, and dietary habits. Traditional Chinese Medicine (TCM) has been increasingly recognized for its potential to manage obesity and diabetes. Weight loss is difficult to sustain, and several diabetic therapies, such as sulfonylureas, thiazolidinediones, and insulin, might make it harder to lose weight. While lifestyle changes should be the primary approach for people interested in lowering weight, drugs are also worth investigating. Since some of the newer glucose-lowering medications that cause weight loss, such as glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and sodium-glucose cotransporter 2 inhibitors (SGLT2i), are additionally utilized or are under consideration for use as anti-obesity drugs, the frontier between glucose-lowering medication and weight loss drugs appears to be shifting. This review provides an overview of the literature on the underlying mechanisms of obesity and diabetes and the prospect of TCM in their management. We discuss the various TCM interventions, including acupuncture, herbal medicine, and dietary therapy, and their effects on metabolic health. We also highlight the potential of TCM in regulating gut microbiota, reducing inflammation, and improving insulin sensitivity. The findings suggest that TCM may provide a promising approach to preventing and managing obesity and diabetes. However, further well-designed studies are needed to confirm the efficacy and safety of TCM interventions and to elucidate their underlying mechanisms of action.